Effect of Fertilization on Fodder Maize (Zea Mays) in Alluvial Soil: Impact of Different Sulphur Sources on Fodder Maize Yield in Alluvial Soil (Journal of Advances and Scholarly Researches in Allied Education, 2017)
An experiment was conducted in alluvial soil of Etawah with Sulphur levels (20, 40, 60 and 80 kg Sha) and sources i.e., ammonium sulphate, pyrite, Gypsum and elemental sulphur including control indicated that the forage yield, nutrient content and their uptake of N, P, S, and Ca by maize increased upto 40 kg Sha. Ammonium sulphate was the best source and gave highest forage yield and uptake of nutrients due to its solubility in water. The application of ammonium sulphate produced maximum forage yield than other sources.With the intensification agriculture and the usages of sulphur free fertilizers the yields of forage crops are often reduced (Aulakh et al., 1977 Singh et al., 1979 Tripathi and Hazra, 1988). In fact, elemental sulphur only was concerned in. crop production, it is costly because imported and takes more time for its transformation in the soil into sulphate by bacteria. Most of the forages are grown for very short period (60-75 days) and require readily available source of this element. There are number of Sulphur containing materials like, gypsum and iron pyrite available in our country and are comparatively cheaper in price. But their efficacy in crop production, especially for fodder crops is yet to be fully assessed.